2005
DOI: 10.1021/tx0501637
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide Trapping of Iminium Ion Reactive Intermediates Followed by Detection and Structure Identification Using Liquid Chromatography−Tandem Mass Spectrometry (LC-MS/MS)

Abstract: Secondary and tertiary alicyclic amines are widely found in pharmaceuticals and environmental compounds. The formation of iminium ions as reactive intermediates in the metabolic activation of alicyclic amines has previously been investigated in radiometric assays where radiolabeled cyanide is typically employed. In this paper, we report a relatively high throughput LC-MS/MS method for the detection of the nonradiolabeled cyanide adduct formed in rat or human liver microsomal incubations via constant neutral lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
132
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 26 publications
15
132
1
Order By: Relevance
“…The 14 mass units appear to be consistent with an additional enzymatic step involving oxidation of the piperazine ring to the corresponding lactam metabolite. An identical finding was also reported by Argoti et al (2005) in their characterization of the cyanide adducts of N-dearylated nefazodone metabolites in rat liver microsomes. Thus the molecular weight of CN2 (MH ϩ ϭ 399; m/z ϭ 274, 246) was consistent with the addition of one molecule of cyanide to the N-dearylated nefazodone M3 (see Table 1) plus the 14-Da mass addition to the piperazine ring.…”
Section: Metabolic Profile Of Nefazodone and Aripiprazole In Human Liversupporting
confidence: 87%
See 3 more Smart Citations
“…The 14 mass units appear to be consistent with an additional enzymatic step involving oxidation of the piperazine ring to the corresponding lactam metabolite. An identical finding was also reported by Argoti et al (2005) in their characterization of the cyanide adducts of N-dearylated nefazodone metabolites in rat liver microsomes. Thus the molecular weight of CN2 (MH ϩ ϭ 399; m/z ϭ 274, 246) was consistent with the addition of one molecule of cyanide to the N-dearylated nefazodone M3 (see Table 1) plus the 14-Da mass addition to the piperazine ring.…”
Section: Metabolic Profile Of Nefazodone and Aripiprazole In Human Liversupporting
confidence: 87%
“…Our present studies on nefazodone metabolism in human liver microsomes and recombinant P4503A4 revealed additional bioactivation pathways involving ␣-carbon oxidation on the piperazine ring in nefazodone and several of its downstream metabolites, yielding reactive iminium ion intermediates. Argoti et al (2005) have also reported a similar finding following nefazodone incubations with rat liver microsomes. Overall, the observations that nefazodone bioactivation by P4503A4 results in the mechanism-based inactivation of the isozyme presumably via covalent modification of an active site nucleophile(s) by reactive quinonoid and/or iminium intermediates (Kalgutkar et al, 2005b) suggests a possibility that these metabolites also can covalently modify macromolecules other than P450, some of which may be essential for critical pathophysiology in the liver.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…20 The trapping reagents used include glutathione (for soft electrophiles such as the quinone imine) as well as methoxylamine and potassium cyanide (for hard electrophiles such as the iminium ion). [21][22][23] Electrochemical oxidation online with electrospray ionization mass spectrometry (EC-ESI/MS) is a relatively new technique that avoids the complexity of working with biological matrices. Electrochemical oxidation has been found to successfully mimic CYP450 benzylic hydroxylation, hydroxylation of aromatic rings containing electron-donating groups, Ndealkylation, S-oxidation, dehydrogenation and, less efficiently, N-oxidation and Odealkylation.…”
Section: <>mentioning
confidence: 99%